Mathematical Modeling of the Expert System Predicting the Severity of Acute Pancreatitis. (9th June 2014) - Ivanchuk, Maria A.; Maksimyuk, Vitalij V.; Malyk, Igor V.
Abstract : The method of building the hyperplane which separates the convex hulls in the Euclidean spaceR n is proposed. The algorithm of prediction of the presence of severity in patients based on this method is developed and applied in practice to predict the presence of severity in patients with acute pancreatitis.